The road to accreditation for fellowship training in regional anesthesiology and acute pain medicine. Issue 5 (October 2018) - Mariano, Edward R.; Rosenquist, Richard W.
Abstract : Purpose of review: The purpose of this review is to provide the background and rationale for pursuing accreditation of regional anesthesiology and acute pain medicine (RAAPM) fellowships, explain specific steps and challenges in the process, and forecast the future of fellowship training. Recent findings: In 2016, the first fellowship program in RAAPM was able to apply for accreditation from the Accreditation Council for Graduate Medical Education (ACGME). The establishment of this newly accredited subspecialty fellowship and the announcement of the first accredited programs represented a tremendous achievement in anesthesiology training and medical education in general and was the culmination of nearly 4 years of dedicated effort. Summary: Programs with initial ACGME accreditation are on a 2-year term and will be reviewed to evaluate adherence to the program requirements and the quality of fellowship training. Deficiencies identified will need to be resolved or face loss of accreditation. However, a program's maintenance of accreditation represents a commitment to its fellows to provide a training experience that can be held as a benchmark for all programs.